Public and Journalist Perception in Surakarta about Covid-19 News Model - Erwin Kartinawati; Betty Gama (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
Mass media adds anxiety to the community regarding Covid-19 news. Some chose not to consume news or did other kinds of counters to reduce the anxiety effect. This study investigated the perception of the public and journalists in Surakarta about Covid-19 news and their perception about the ideal reporting model in a situation such as this time. Agenda setting media theory was used to understand the issue explored. Data were collected using questionnaire and interview. This research concluded that media was considered a cause of psychological disorders, especially anxiety and fear, because of the bad news. The media was still not sensitive to public needs as news tends to pursue ratings/compete to find viewers by making excessive or bombastic titles. The expected news model shall prioritize facts and minimize the negative impact through optimistic news; educational; clear and complete information by credible sources; used terms that were understood by all; showed empathy, sympathy; and content variation.